Kebijakan Pengembangan Koleksi UPT. Perpustakaan Universitas Islam Negeri Sultan Syarif Kasim Riau - Rasdanelis Rasdanelis (Pustabiblia: Journal of Library and Information Science, 2022)
Collection development policy is a basic concept and principle in the form of outlines as a guide and direction for planning in the development of library collections. This study aims to find out how the collection development policy and collection development mechanism at UPT Library Sultan Syarif Kasim Riau. This study used a qualitative descriptive approach, data were collected using interview, observation and documentation techniques. Interviews were conducted with the head of the library and librarians at the library of UIN Sultan Syarif Kasim Riau. The next stage is  the data from observations, interviews, and documentation processed and analyzed using qualitative descriptive techniques. Based on the data from the research and  discussion, it is known that the UPT Library of UIN Sultan Syarif Kasim Riau does not yet have a written collection development policy approved by the university leadership. Collection development policies and mechanisms are implemented based on the experience and understanding of the head of the library and librarian regarding the theoretical concepts of collection development policy. Policies like this have an impact on the unfulfilled needs of library collections, both in terms of number, recency and relevance.